2014
DOI: 10.1177/0021998314541312
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of adhesive layer behavior in patch-repaired carbon fiber-reinforced polymer panel involving digital image correlation

Abstract: In the present work, critical strain field in thin adhesively layer of double-sided (symmetrical) patch-repaired carbon fiber-reinforced polymer composite panel under tensile load is investigated using digital image correlation technique. Longitudinal, peel, and shear-strain distribution in adhesive layer is analyzed thoroughly in repaired panel by performing global cum local strain field analysis involving digital image correlation. Effective load/shear transfer length in repair configuration is estimated bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Digital image correlation (DIC) technique is widely used in laminated as well as metallic structures for damage evaluation and detects surface strain in the composite patch repair (Caminero et al , 2012, 2013; Kashfuddoja and Ramji, 2015; Pavlopoulou et al , 2016). Experimental analysis requires the involvement of sophisticated instruments such as digital image correlation and digital photoelasticity techniques for measurement of the stress intensity around the crack tip and interfacial stresses in the adhesive layer.…”
Section: Introductionmentioning
confidence: 99%
“…Digital image correlation (DIC) technique is widely used in laminated as well as metallic structures for damage evaluation and detects surface strain in the composite patch repair (Caminero et al , 2012, 2013; Kashfuddoja and Ramji, 2015; Pavlopoulou et al , 2016). Experimental analysis requires the involvement of sophisticated instruments such as digital image correlation and digital photoelasticity techniques for measurement of the stress intensity around the crack tip and interfacial stresses in the adhesive layer.…”
Section: Introductionmentioning
confidence: 99%
“…M. Kashfuddoja and M. Ramji studied the critical strain field in the thin adhesive layer using DIC. Their results were compared with finite element analysis results 20) . They concluded that DIC can accurately analyze the strain field of adhesive joint specimens.…”
Section: Introductionmentioning
confidence: 99%